Effectiveness of fall prevention interventions in residential aged care and community settings: an umbrella review - Isabelle Meulenbroeks; Crisostomo Mercado; Peter Gates; Amy Nguyen; Karla Seaman; Nasir Wabe; Sandun M Silva; Wu Yi Zheng; Deborah Debono; Johanna Westbrook (BMC Geriatrics, 2024)
Abstract Introduction Preventing falls is a priority for aged care providers. Research to date has focused on fall prevention strategies in single settings (e.g., residential aged care (RAC) or community settings). However, some aged care providers deliver care, including fall prevention interventions, across RAC and community settings. We conducted an umbrella review to identify what type of fall prevention interventions had the greatest impact on falls outcomes in RAC and community settings. Methods Five databases were searched for systematic reviews of falls prevention randomised control trials in older adults living in the community or RAC. Data extracted included systematic review methods, population characteristics, intervention characteristics, setting details (RAC or community), and fall-related outcomes (falls, people who have had a fall, fall-related hospitalisations, and fall-related fractures). Review quality was appraised using the Assessment of Multiple Systematic Reviews-2 tool. Results One-hundred and six systematic reviews were included; 63 and 19 of these stratified results by community and RAC settings respectively, the remainder looked at both settings. The most common intervention types discussed in reviews included ‘exercise’ (61%, n = 65), ‘multifactorial’ (two or more intervention types delivered together) (26%, n = 28), and ‘vitamin D’ (18%, n = 19). In RAC and community settings, ‘exercise’ interventions demonstrated the most consistent reduction in falls and people who have had a fall compared to other intervention types. ‘Multifactorial’ interventions were also beneficial in both settings however demonstrated more consistent reduction in falls and people who fall in RAC settings compared to community settings. ‘Vitamin D’ interventions may be beneficial in community-dwelling populations but not in RAC settings. It was not possible to stratify fall-related hospitalisation and fall-related fracture outcomes by setting due to limited number of RAC-specific reviews (n = 3 and 0 respectively). Conclusion ‘Exercise’ interventions may be the most appropriate falls prevention intervention for older adults in RAC and community settings as it is beneficial for multiple fall-related outcomes (falls, fall-related fractures, and people who have had a fall). Augmenting ‘exercise’ interventions to become ‘multifactorial’ interventions may also improve the incidence of falls in both settings.